2012
DOI: 10.1089/met.2012.0031
|View full text |Cite
|
Sign up to set email alerts
|

Is the Metabolic Syndrome a “Small Baby” Syndrome?: The Bogalusa Heart Study

Abstract: Background: Metabolic syndrome has been called a ''small baby syndrome,'' but other analyses suggest that postnatal growth is more important than birthweight, or that large babies are also at risk. The aim of this analysis was to examine whether there was a relationship between both low and high birthweight and metabolic syndrome, using multiple definitions of metabolic syndrome, and to determine whether this relationship varied by body size across the life course. Methods: Data from the Bogalusa Heart Study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…[31][32][33] However, postnatal obesity, diabetes mellitus, or metabolic syndrome affect, in a highly heterogeneous manner, subjects who were born with a low birthweight and these conditions are actually uncommon in some reported cohorts. 34,35 Consequently, although metabolic programming must be a contributing factor, it cannot explain per se the epidemiologic association between FGR and CVDs. 36 Over the last 10 years, a second important line of evidence has shown that FGR is also associated with direct changes in the cardiovascular system.…”
Section: Fetal Programming Of Adult Cardiovascular Diseasementioning
confidence: 99%
“…[31][32][33] However, postnatal obesity, diabetes mellitus, or metabolic syndrome affect, in a highly heterogeneous manner, subjects who were born with a low birthweight and these conditions are actually uncommon in some reported cohorts. 34,35 Consequently, although metabolic programming must be a contributing factor, it cannot explain per se the epidemiologic association between FGR and CVDs. 36 Over the last 10 years, a second important line of evidence has shown that FGR is also associated with direct changes in the cardiovascular system.…”
Section: Fetal Programming Of Adult Cardiovascular Diseasementioning
confidence: 99%
“…These works are calling for in vivo assessment of miRNA functionality when delivered by natural or biomimetic nanoparticles in order to control metabolic diseases from infancy to adulthood. Indeed, improper nutritional handling of preterm babies is a general health problem in the World ( 76 ) leading to the onset of a metabolic syndrome through nutritional programming. Epidemiological analysis ( 77 ) suggest that human milk is better than artificial infant formula by allowing appropriate nutritional programming and protecting the baby against diseases of civilization in later life (T2D, obesity, hypertension).…”
Section: Detection Of Mirna In Exosomes Associated With Type-2 Diabetmentioning
confidence: 99%
“…It is now well established that events occurring during early life can also impact on long term levels of blood pressure and cardiovascular health [ 8 , 9 , 10 , 11 ], with impaired growth in early life leading to long term vulnerability to cardiovascular disease. Over recent decades many epidemiological studies have linked low birth weight with long term heart disease [ 12 , 13 , 14 , 15 , 16 , 17 ] and with other disease processes that are directly associated with an increased propensity for cardiovascular disease, such as metabolic disease [ 18 , 19 ], insulin resistance [ 20 , 21 ], non-insulin dependent diabetes [ 22 , 23 ], renal disease [ 24 ] and hypertension [ 25 , 26 ].…”
Section: Low Birth Weight Is Linked To Long-term Cardiovascular DImentioning
confidence: 99%